Applicant characteristics and interview-day structure of shoulder and elbow surgery fellowships. Issue 6 (9th November 2022) - Haislup, Brett D.; McCormick, Brian P.; Smith, Brandon; Wright, Melissa A.; Murthi, Anand M.
Abstract : Background: The purpose of this study was to determine the selection criteria and interview-day structure used by shoulder and elbow fellowship program directors. Methods: An anonymous 14-question survey was distributed to the program directors of the 31 American Shoulder and Elbow Surgeons (ASES) recognized orthopaedic shoulder and elbow fellowship programs. Surveys were sent via email, and responses were collected from March 31, 2021 to May 10, 2021. Results: All 31 fellowship directors responded (100%). The most valuable selection criteria for applicants were subjective measures: quality of interview, letters of recommendation, and quality of residency program. Objective criteria such as United States Medical Licensing Examination (USMLE) scores and Orthopaedic In-Training Examination (OITE) scores were less important. Fifteen (50%, 15/30) programs required applicants to have one to two publications, while 15 (50%, 15 of 30) required three to five publications. Programs most commonly interviewed 16 to 20 residents (38.7%). The interview day was a half day for the majority of programs (n=20; 64.5%), with most programs utilizing three (25.8%) or four (45.2%) separate interviews. Current fellows interviewed applicants in about half of the programs (51.6%). Conclusions: Shoulder and elbow fellowship program directors prioritize subjective over objective attributes when selecting applicants. The interview day is most commonly a half day with each applicant undergoing multiple interviews at each institution. Understanding the selection process used by shoulder and elbow fellowship directors provides a valuable resource for residents. Level of Evidence: Level V.